Governance of flood disaster framework: A way forward using the framework - Maidin, Siti Sarah; Othman, Marini; Ahmad, Mohamad Nazir (Universiti Utara Malaysia (UUM), 2017)
Weakness in the governance component within a flood man-agement system will jeopardize the works of the system as a whole. Specific to flood management, poor governance reflects weakness in tracking and monitoring of flood activities and systems, poor mitigation of flood risk, and non-optimal use of given (as well as investment) resources. This study pro-poses a governance framework to govern the flood disaster in Malaysia. The Control Objective for Information and Related Technologies, Hyogo Framework for Action, and Sendai Framework for Disaster Risk Reduction principles were used as guiding principles for the development of the pro-posed framework. A qualitative field study was deployed for the identifica-tion of baseline practices in governing the flood in Malaysia. As a result, Governance for Flood Disaster framework which consist of ten (10) build-ing blocks components were constructed. It is hoped that further studies can be undertaken to develop and establish each of the components within the framework and that the framework itself can be further tested and improved over time.